Genome-Wide Association Study Reveals the Genetic Architecture Underlying Salt Tolerance-Related Traits in Rapeseed (Brassica napus L.) - Wan, Heping; Chen, Lunlin; Guo, Jianbin; Li, Qun; Wen, Jing; Yi, Bin; Ma, Chaozhi; Tu, Jinxing; Fu, Tingdong; Shen, Jinxiong (Frontiers in Plant Science, 2017)
Soil salinity is a serious threat to agriculture sustainability worldwide. Salt tolerance at the seedling stage is a crucial prerequisite for plant establishment and high yield in saline soils; however, little information is available on rapeseed (Brassica napus L.) salt tolerance. We evaluated salt tolerance in different rapeseed accession and conducted a genome-wide association study (GWAS) to identify salt tolerance-related quantitative trait loci (QTLs). A natural population comprising 368 B. napus cultivars and inbred lines was genotyped with a Brassica 60K Illumina Infinium SNP array ; 75 single-nucleotide polymorphisms (SNPs) distributed across 14 chromosomes were associated with four salt tolerance-related traits. These SNPs integrated into 25 QTLs that explained 4.21–9.23% of the phenotypic variation in the cultivars. Additionally, 38 possible candidate genes were identified in genomic regions associated with the salt tolerance indexes; these fell into several functional groups including transcription factors, aquaporins, transporters, and enzymes, all play a role in salt tolerance in A. thaliana, rice, and other crops. Thus, salt tolerance in rapeseed involves complex molecular mechanisms. Our results provide valuable information for studying the genetic control of salt tolerance in B. napus seedlings and may facilitate marker-based breeding for rapeseed salt tolerance.